Reflective Guarded Horn Clauses language implementation and programming - Tanaka, Jiro; Matono, Fumio (1991)
Abstract: "We consider the meta-level representation of Guarded Horn Clauses (GHC) first. We implement GHC meta-computation system by enhancing the simple 4-line GHC meta-program. Then we describe Reflective Guarded Horn Clauses (RGHC) system, where reflective tower can be constructed and collapsed in a dynamic manner. This system has the following two features comparing to the previous approaches: First, this system is formulated without using quote. Secondly, it has the reflective mechanism in which reflective tower can be constructed using reflective predicates. RGHC has actually been implemented. A simple execution example is also shown in this paper
Keywords: GHC (Computer program language)